(untitled) (CIPEEX, 2022)
&NBSP; CAFFEINE, ALSO KNOWN AS THEINE, GUARAIN OR MATEIN, IS A SUBSTANCE FOUND IN MORE THAN 60 PLANT SPECIES. IT IS FOUND ON A DAY-TO-DAY HIGH IN COMMON FOODS AND BEVERAGES SUCH AS COFFEE, CHOCOLATE, SOFT DRINKS AND TEAS. IT IS POPULARLY KNOWN IN THE MARKET AS A STIMULATING AND WELL-KNOWN SUBSTANCE. THIS RESEARCH WAS CARRIED OUT WITH THE OBJECTIVE OF INVESTIGATING THE IMPROVEMENT OF PERFORMANCE DURING EXERCISES. THE SEARCH FOR BIBLIOGRAPHIC REFERENCES WAS MADE IN THE PUBMED DATABASE, IN ORIGINAL ARTICLES PUBLISHED BETWEEN 2012 AND 2022, USING THE KEYWORDS: CAFFEINE, PERFORMANCE AND MUSCLE ENDURANCE. THE IMPORTANCE OF THE ERGOGENIC BENEFITS OBTAINED WITH CAFFEINE SEEMS SIMILAR IN WOMEN AND MALE ATHLETES. IN GENERAL, CURRENT SYSTEMIC REVIEWS PROVIDE EVIDENCE OF THE EFFICACY OF CAFFEINATED BEVERAGES AS A VALID FORM OF CAFFEINE SUPPLEMENTATION IN SPORTS, PROVING BETTER PERFORMANCE IN TRAINING, ALTHOUGH NO EFFECTS ON MUSCLE STRENGTH ARE IDENTIFIED. IN ADDITION, THEY REVEALED THAT CAFFEINE HAS A CLEAR EFFECT ON HANDGRIP STRENGTH IN COMBAT SPORTS, ALTHOUGH IT IS A SMALL EFFECT. IMPROVEMENT IN PSYCHOMOTOR SURVEILLANCE HAS ALSO BEEN VERIFIED.&NBSP; SIDE EFFECTS WERE NOT RELEVANT COMPARED TO THOSE PRESENTED IN PLACEBOS. IN ADDITION TO CAFFEINE SUPPLEMENTATION, THE EFFICACY OF CAFFEINATED BEVERAGES IN THE USE OF SPORTS WAS VERIFIED, IMPROVING PERFORMANCE.